The influence of framing effect and clawback provision on divestment decision making: An experimental study - Misra, Fauzan; Victory, Galant (Journal of Accounting and Investment, 2026)
Research aims: This study analyzes the dual impact of framing (positive versus negative) and clawback provisions on managerial decisions regarding divestment. The study focuses on the interaction between clawback provisions, which serve as compensation-related loss cues, and externally framed accounting information, and its impact on managers’ risk attitudes regarding negative performance investments.Design/Methodology/Approach: A 2×2 between-subjects laboratory experiment was conducted with 84 participants who evaluated divestment alternatives under positive or negative frames, with or without clawback provisions.Research findings: The results indicate that framing significantly influences divestment decisions, as positive frames lead to risk-averse divestment choices, while negative frames promote risk-seeking continuation. Although clawback provisions do not exhibit a significant main effect, their interaction with framing is significant. Clawbacks increase risk-taking under positive frames but reduce risk-taking under negative frames, revealing a novel dual-framing mechanism.Theoretical contribution/Originality: This study demonstrates empirically that the behavioral consequences of clawback provisions vary depending on the framing of performance evaluation information. The study demonstrates that compensation-based loss signals interact with information framing, extending behavioral accounting research on framing effects to the area of divestment decisions in non-financial contexts.Practical implications: The results suggest that firms should better align their pay contracts with their internal reporting structures. More specifically, integrating clawback provisions with performance accomplishments articulated in positive terms may lead managers to persist in their failure to lose investments. Hence, firms and pay committees need to align the design of incentives with management reporting to contain loss-inducing risk-taking.